2022
DOI: 10.3389/fphar.2022.1070473
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and behaviors regarding online pharmacies in the aftermath of COVID-19 pandemic: At the tipping point towards the new normal

Abstract: The COVID-19 pandemic accelerated the online purchase of goods and services in which today’s e-pharmacy is now an integral part of healthcare provisions in developed countries. The aim of our research was to assess the frequency and attitudes of European consumers purchasing medications online prior to and following the pandemic in the Visegrad Group countries (V4). An online cross-sectional study was conducted between May-August 2022. A 25-item questionnaire with single choice and 5-point Likert scale answers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 21 publications
0
16
1
2
Order By: Relevance
“…It contrasts with traditional “brick and mortar” pharmacies, which are associated with longer queues, less privacy, and shorter opening times. Additionally, the COVID-19 pandemic has accelerated the purchase of medicines via the internet [ 3 ]. A study conducted by researchers from Hungary found that the rate of medicines purchased on the internet increased from 4.2% in 2018 to 44.2% in March 2020 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It contrasts with traditional “brick and mortar” pharmacies, which are associated with longer queues, less privacy, and shorter opening times. Additionally, the COVID-19 pandemic has accelerated the purchase of medicines via the internet [ 3 ]. A study conducted by researchers from Hungary found that the rate of medicines purchased on the internet increased from 4.2% in 2018 to 44.2% in March 2020 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the COVID-19 pandemic has accelerated the purchase of medicines via the internet [ 3 ]. A study conducted by researchers from Hungary found that the rate of medicines purchased on the internet increased from 4.2% in 2018 to 44.2% in March 2020 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…La concientización ciudadana se sugiere como estrategia de intervención temprana para controlar la venta de este tipo de productos ( 9 , 10 ). Las campañas de radio y televisión pueden ser efectivas para aumentar la conciencia.…”
Section: Resultsunclassified
“…Aunque la venta en línea de medicamentos tiene el aparente potencial de mejorar el acceso a los productos médicos, ofrecer transparencia de precios, y considerar las preferencias y privacidad del consumidor, tal y como se observó en el contexto de la pandemia por COVID-19 ( 9 ), es necesario enmarcar esta opción de comercio con instrumentos legales y regulatorios adecuados, y una estrategia conjunta entre las Autoridades Reguladoras Nacionales (ARN) , las autoridades de comercio y la sociedad civil para proteger la seguridad de los pacientes ( 8 ).…”
unclassified
“…According to the representative direct questionnaire survey of Fittler et al the respondents (n = 1055) already bought medicines (4.17 %) and other health products (18.4 %) via the internet ( Fittler et al, 2018a ). A significant increase in the frequency of buying medicines (55.48%) and health products (63.0%) online was measured in a recent online survey following the coronavirus pandemic ( Fittler et al, 2022 ). There are numerous patient safety risks associated with obtaining medicines outside the official supply chains.…”
Section: Introductionmentioning
confidence: 99%